India : 2012 Article IV Consultation-Staff Report; Staff Statement and Supplements; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for India. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This Article IV Consultation reports that India's growth remains relatively high, but various factors, including the unsettled global outlook and slow government decision making, have weighed on investment. Inflation has moderated, leading the Reserve Bank of India (RBI) to pause monetary tightening, but remains elevated. The slow pace of fiscal consolidation has added to demand pressures. Ensuring sustainable growth will require reinvigorating the structural agenda, rather than relying on monetary and fiscal stimulus. Measures to facilitate infrastructure investment, reform the financial sector and labor markets, and address agricultural productivity and skills mismatches stand out.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet